Short Review of Oligosaccharides Application from Local Indonesian Tubers as Prebiotic - Rifqi Ahmad Riyanto; Ainun Nafisah (Journal of Food and Agricultural Product, 2022)
The application of prebiotics in processed food and feed has been widely carried out as an effort to improve the health level of humans and livestock. This literature review aims to provide an overview of the development of the use of local Indonesian tubers and their oligosaccharide content for prebiotic applications in food and feed. The results showed that local Indonesian tubers contain oligosaccharides among groups such as inulin, raffinose, glucomannan, and lactulose. Its applications in food processing include synbiotic yogurt and salami. While its prebiotic properties can also be applied as animal feed.Keywords: tubers, local, oligosaccharide, food, feed